PERAN PEMANFAATAN TEKNOLOGI PENDIDIKAN DALAM MENINGKATKAN KUALITAS BELAJAR DI MADRASAH TSANAWIYAH NURUL QUR’AN - Naafi’u Annurun, Naafi’u Annurun (Institut Agama Islam Riyadhlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
Educational technology or learning technology is a tool to facilitate the teaching and learning process and improve performance through its use and management of technology. Educational technology can change the learning and teaching process in various school institutions, both elementary and middle level (SMA). Educational technology can make it possible to change students in learning both in various tasks or materials that they may not be able to see directly by the teacher. Technology is also a practice and development, utilization, and evaluation in the learning process. By incorporating educational technology into learning, students will find it easier to do school assignments. Educators can provide technology for students to provide learning experiences to students that may be able to realize student desires. The use of educational technology must be adapted to educational goals that involve the use of technology that can change the role of educators and students in improving thinking skills and solving problems. Educational technology really supports the teaching and learning process, because attractive learning media is a means to improve the quality of education. Educational technology has good facilities and educational media can improve the quality of education, make learning more efficient, effective and get maximum results from the teaching and learning process. Especially in this day and age the use of educational technology is very useful because it can make it easier for students when learning when they are not face to face and educational technology is now also growing rapidly. Educational technology is expected to increase learning innovation and can facilitate students in various learning problems. If learning is as effective, efficient and better, the learning process will be realized optimally.